Antibiofilm Evaluation of Two Different Denture Liners Incorporated with Zirconium Oxide Nanoparticles - Aysel Uğur; Gulfem Ergun; Ayşe Seda Ataol; Zeynep Şahin; Nurdan Saraç; Tuba Baygar (Cumhuriyet University, 2022)
Abstract Objectives: This in vitro study was purposed to examine the effects of incorporation nano-ZrO2 on antibiofilm activity, glucose sorption, weight change, and surface roughness of two different types of denture liners. Materials and Methods: Modified nano-ZrO2 were added to silicone-based and acrylic resin-based prosthetic lining materials at two different concentrations (0.5% and 1%). The antibiofilm potentials of test groups against Candida albicans (C. albicans), Staphylococcus aureus (S. aureus), and Streptococcus mutans (S. mutans) were determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) method. Surface roughness, weight change, and glucose sorption of denture liners were also evaluated after modifying with nano-ZrO2. Results: According to the antibiofilm activity results, 1% nano-ZrO2 addition to silicon-based and acrylic resin-based denture liners resulted in 16.48% and 13.39% of biofilm inhibition for S. aureus, respectively. 1% nano-ZrO2 addition to silicon-based denture liners also inhibited the S. mutans biofilm formation at an 8.16% rate. Nano-ZrO2 addition to the test groups had no inhibition effect on C. albicans biofilm formation. Surface roughness decreased significantly once nano-ZrO2 was added in tissue conditioner test groups (p=0.012), however, the addition of 0.5% nano-ZrO2 increased soft denture liner test group significantly (p<0.001). Conclusions: To overcome the microbial biofilm problems (especially against S. aureus and S. mutans) caused by the use of denture liners, addition of nano-ZrO2 might be a promising agent with its antibiofilm capacities.